The antihypertentive effect of aqueous extract O Africana leaves - Wang, Xu (University of the Western Cape, 2013)
Magister Scientiae - MSc === The incidence of cardiovascular diseases, including hypertension, is on the increase worldwide. Medicinal plants played an important role in the treatment of hypertension for centuries. Very few scientific studies have, however, been done to validate the use of these phytotherapies. O africana is on of the many phytotherapies that has been use indigenously for years to treat hypertension. The objectives of this study were to determine the most effective does of O africana aqueous extract which will reduce blood pressure; to determine whether chronic administration of O africana can be used to prevent and treat hypertension; to determine whether O africana exert its effects by modulation of the renin-angiotensin system. === South Africa